A Pivotal Study of Optoacoustic Imaging to Diagnose Benign and Malignant Breast Masses: A New Evaluation Tool for Radiologists - Neuschler, Erin I.; Butler, Reni; Young, Catherine A.; Barke, Lora D.; Bertrand, Margaret L.; Böhm-Vélez, Marcela; Destounis, Stamatia; Donlan, Pamela; Grobmyer, Stephen R.; Katzen, Janine; Kist, Kenneth A.; Lavin, Philip T.; et al. (Radiology, 2018)
Purpose To compare the diagnostic utility of an investigational optoacoustic imaging device that fuses laser optical imaging (OA) with grayscale ultrasonography (US) to grayscale US alone in differentiating benign and malignant breast masses. Materials and Methods This prospective, 16-site study of 2105 women (study period: 12/21/2012 to 9/9/2015) compared Breast Imaging Reporting and Data System (BI-RADS) categories assigned by seven blinded independent readers to benign and malignant breast masses using OA/US versus US alone. BI-RADS 3, 4, or 5 masses assessed at diagnostic US with biopsy-proven histologic findings and BI-RADS 3 masses stable at 12 months were eligible. Independent readers reviewed US images obtained with the OA/US device, assigned a probability of malignancy (POM) and BI-RADS category, and locked results. The same independent readers then reviewed OA/US images, scored OA features, and assigned OA/US POM and a BI-RADS category. Specificity and sensitivity were calculated for US and OA/US. Benign and malignant mass upgrade and downgrade rates, positive and negative predictive values, and positive and negative likelihood ratios were compared. Results Of 2105 consented subjects with 2191 masses, 100 subjects (103 masses) were analyzed separately as a training population and excluded. An additional 202 subjects (210 masses) were excluded due to technical failures or incomplete imaging, 72 subjects (78 masses) due to protocol deviations, and 41 subjects (43 masses) due to high-risk histologic results. Of 1690 subjects with 1757 masses (1079 [61.4%] benign and 678 [38.6%] malignant masses), OA/US downgraded 40.8% (3078/7535) of benign mass reads, with a specificity of 43.0% (3242/7538, 99% confidence interval [CI]: 40.4%, 45.7%) for OA/US versus 28.1% (2120/7543, 99% CI: 25.8%, 30.5%) for the internal US of the OA/US device. OA/US exceeded US in specificity by 14.9% (P < .0001; 99% CI: 12.9, 16.9%). Sensitivity for biopsied malignant masses was 96.0% (4553/4745, 99% CI: 94.5%, 97.0%) for OA/US and 98.6% (4680/4746, 99% CI: 97.8%, 99.1%) for US (P < .0001). The negative likelihood ratio of 0.094 for OA/US indicates a negative examination can reduce a maximum US-assigned pretest probability of 17.8% (low BI-RADS 4B) to a posttest probability of 2% (BI-RADS 3). Conclusion OA/US increases the specificity of breast mass assessment compared with the device internal grayscale US alone. Online supplemental material is available for this article. RSNA, 2017.